2013
DOI: 10.5194/acp-13-9159-2013
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of very low frequency (VLF) radio wave signal profile due to solar flares using the GEANT4 Monte Carlo simulation coupled with ionospheric chemistry

Abstract: Abstract. X-ray photons emitted during solar flares cause ionization in the lower ionosphere (~60 to 100 km) in excess of what is expected to occur due to a quiet sun. Very low frequency (VLF) radio wave signals reflected from the D-region of the ionosphere are affected by this excess ionization. In this paper, we reproduce the deviation in VLF signal strength during solar flares by numerical modeling. We use GEANT4 Monte Carlo simulation code to compute the rate of ionization due to a M-class flare and a X-cl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
37
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 35 publications
1
37
0
Order By: Relevance
“…The connection between the solar flares and the signal parameters has been widely studied [Nicolet and Aiken, 1960;Crombie, 1965;Yonezawa, 1966;Mitra, 1974Mitra, , 1981Zigman et al, 2007;Schmitter, 2013]. In addition to the data analysis, numerical models were proposed to simulate the electron density enhancement [Rowe et al, 1974;Glukhov et al, 1992;Palit et al, 2013]. In other works, the authors used the LWPC code [Ferguson, 1998] and the signal parameters to infer the electron density increases in relation with the solar flares flux [McRae and Thomson, 2000Thomson, , 2004Grubor et al, 2005Grubor et al, , 2008Thomson et al, 2005;Han and Cummer, 2010;Thomson et al, 2011].…”
Section: Introductionmentioning
confidence: 99%
“…The connection between the solar flares and the signal parameters has been widely studied [Nicolet and Aiken, 1960;Crombie, 1965;Yonezawa, 1966;Mitra, 1974Mitra, , 1981Zigman et al, 2007;Schmitter, 2013]. In addition to the data analysis, numerical models were proposed to simulate the electron density enhancement [Rowe et al, 1974;Glukhov et al, 1992;Palit et al, 2013]. In other works, the authors used the LWPC code [Ferguson, 1998] and the signal parameters to infer the electron density increases in relation with the solar flares flux [McRae and Thomson, 2000Thomson, , 2004Grubor et al, 2005Grubor et al, , 2008Thomson et al, 2005;Han and Cummer, 2010;Thomson et al, 2011].…”
Section: Introductionmentioning
confidence: 99%
“…Along with many terrestrial influences, the Sun is the predominant extraterrestrial driver of various dynamic evolution at this part of the atmosphere. Apart from the fact that the ionosphere itself is the result of the ionizing interaction mainly of solar ultraviolet radiation (Nicolet & Aikin, 1960;Watanabe, 1958;Watanabe et al, 1955), the effect of X-rays from solar flares and energetic particles from various solar eruptive events, like flares and coronal mass ejection (CME), has been studied extensively (Kolarski & Grubor, 2014;Liu et al, 1996;Mariska & Oran, 1981;McRae & Thomson, 2004;Palit et al, 2013Palit et al, , 2015Thomson & Clilverd, 2001;Velinov et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The efforts of interpreting or modeling the observed VLF signal modulation by calculating the influence of source radiation on the ionospheric or atmospheric parameters and then estimating the corresponding changes in propagation characteristic are handful. Along the line of the later approach, Palit et al (2013) presented one such model calculations for the observed amplitude modulation during a X and a M class solar flare. Palit et al (2015) also formulated and quantified the observed delay between peaks of the flare X-ray and the corresponding sudden ionospheric disturbances (SIDs), in terms of the flare parameters (like intensity and sharpness of the incident X-ray lightcurve) and atmospheric reaction rate coefficients.…”
Section: Introductionmentioning
confidence: 99%
“…This is one of the major assumptions for the numerical modelling as used by various scientist such as Hayakawa et al (1996), , Clilverd et al (1999), Rodger et al (1999). Also in numerical modelling, this assumption was used in a vast scale by Budden (1961), Baba et al (1998), Wait and Spices (1964), Pal et al (2012), Basak and Chakrabarti (2013), Palit et al (2013). It is obvious that the decrease in the reflection height modified the total path length of the radio wave and this changes the phase of the VLF signal.…”
Section: Introductionmentioning
confidence: 99%
“…During solar flares, strong ionization increases the electron density of the order of 1-2. The signal amplitude and phase in-general suffers a sharp rise with an exponential decay due to a solar flare (Palit et al 2013;Mitra 1974;Grubor et al 2005). VLF propagation is generally characterized by low attenuation, high phase and frequency stability, and high signal to noise ratio.…”
Section: Introductionmentioning
confidence: 99%